Enhanced growth of Nd3+:MgGdB5O10 laser crystals with intense multi-wavelength emission characteristics. Issue 21 (29th April 2020) - Sun, Shijia; Wei, Qi; Huang, Yisheng; Yuan, Feifei; Lou, Fei; Zhong, Degao; Zhang, Lizhen; Lin, Zhoubin; Teng, Bing
Abstract : Higher quality Nd:GMB crystals were obtained using enhanced K2 Mo3 O10 –B2 O3 flux. Intense multi-wavelength emissions reveal their potential in THz technology. Abstract : Nd 3+ -doped GdMgB5 O10 (Nd:GMB) crystals with better crystalline quality were grown successfully using the enhanced flux of K2 Mo3 O10 –B2 O3 instead of previous NaF flux by the top-seeded solution growth method. A systematic investigation of crystal structures, thermal and mechanical properties, polarized absorption spectra, fluorescence spectra and lifetimes was reported in detail. The main spectroscopic parameters of Nd 3+ ions in GMB crystals, such as J–O intensity, line strengths, spontaneous transition rates, fluorescence branching ratios and radiative lifetimes, were calculated systematically based on J–O theory. The large thermal conductivity (5.3 W mK −1, RT), specific heat (0.71 J gK −1, RT) and Mohs' hardness (6.38, RT) make Nd:GMB more suitable for high-power laser systems. The broad absorption FWHM (22.3 nm) at around 800 nm matches very well with the emission wavelength of AlGaAs laser diodes. Five strong emission peaks located at 1053, 1066, 1074, 1080 and 1087 nm can be observed obviously in polarized fluorescence spectra. The intense spectral anisotropy and multi-wavelength emission characteristics indicate that Nd:GMB is a promising multi-wavelength laser crystal. Specifically, orthogonally polarized dual-wavelength lasers may be able to be used as light sources for the generation of THz radiation.